Development of Solar Energy in Sabah Malaysia: The Case of Trudgill’s Perception (International Journal of Sustainable Energy and Environmental Research, 2014)
Solar energy in Malaysia was first introduced as one of the five fuels in electricity generation through the Fifth Fuel Policy in 2001. However, the current real harnessing of available solar sources is still below its actual potential. This study examined the non-technical barriers towards solar energy implementation in Sabah located on the Borneo Island on eastern part of Malaysia. Following the theoretical framework, the proposed non-technical barriers are agreement, knowledge, technological, economic, social and political. The results of the study showed that awareness and economics are among the two significant barriers in solar energy implementation in Sabah. This necessitates more appropriate energy and financial policies to help public acceptance of solar energy sources for electricity generation in the region.